2019
DOI: 10.3390/ijms20153768
|View full text |Cite
|
Sign up to set email alerts
|

Propolis Reduces the Expression of Autophagy-Related Proteins in Chondrocytes under Interleukin-1β Stimulus

Abstract: Background: Osteoarthritis (OA) is a progressive and multifactorial disease that is associated with aging. A number of changes occur in aged cartilage, such as increased oxidative stress, decreased markers of healthy cartilage, and alterations in the autophagy pathway. Propolis extracts contain a mixture of polyphenols and it has been proved that they have high antioxidant capacity and could regulate the autophagic pathway. Our objective was to evaluate the effect of ethanolic extract of propolis (EEP) on chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 96 publications
(147 reference statements)
1
19
0
Order By: Relevance
“…This increase is thought to be an adaptive response to protect cells from stress and regulate changes in OA-related gene expression through modulation of apoptosis and ROS during the phase initial degenerative OA, but in cases of severe damage autophagy would decrease [ 37 , 43 ]. In addition, it has been observed that the inflammatory stimulus with IL-1β in chondrocytes increases the LC3I protein expression similar to the one that was observed with the autophagy inducer, rapamycin, and this excessive or prolonged activation could promote cell death [ 44 ], these results are consistent with other studies [ 39 , 40 , 41 ].…”
Section: Autophagy and Osteoarthritissupporting
confidence: 89%
See 2 more Smart Citations
“…This increase is thought to be an adaptive response to protect cells from stress and regulate changes in OA-related gene expression through modulation of apoptosis and ROS during the phase initial degenerative OA, but in cases of severe damage autophagy would decrease [ 37 , 43 ]. In addition, it has been observed that the inflammatory stimulus with IL-1β in chondrocytes increases the LC3I protein expression similar to the one that was observed with the autophagy inducer, rapamycin, and this excessive or prolonged activation could promote cell death [ 44 ], these results are consistent with other studies [ 39 , 40 , 41 ].…”
Section: Autophagy and Osteoarthritissupporting
confidence: 89%
“…In the pharmacological aspect, there are no drugs available that are capable of modifying OA and there are a large number of drug candidates in clinical trials that have failed to demonstrate efficacy or are associated with adverse effects [ 1 ]. The most used pharmacological treatments in OA are generally symptomatic and focus on non-steroidal anti-inflammatory drugs (NSAIDs) and analgesics [ 44 , 48 ] and COX-2 inhibitors such as rofecoxib, that decrease pain but cannot stop disease progression, and intra-articular glucocorticoid and hyaluronic acid injections that decrease pain but may also increase disease progression [ 49 ]. For this reason, other therapeutic alternatives are necessary to prevent or decrease the progression of OA, avoiding the side effects of most treatments and focusing on the multimodal and progressive nature of OA [ 50 ].…”
Section: Autophagy and Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis (OA) is a chronic progressive, degenerative, and multifactorial diarthrodial joint disease that mostly affects the hips, knees, hands, and feet [ 1 , 2 , 3 ]. This disorder is ranked as the second leading cause of disability in the world by the World Health Organization (WHO) and it causes a progressive loss and degradation of articular cartilage, development of osteophyte, subchondral bone sclerosis, and synovial inflammation [ 1 , 4 ]. OA incidence is rising at an alarming rate, with it being estimated that 35% of the world’s population will suffer from this condition by 2030 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several therapeutic strategies have been developed and proposed to improve the restoration of the articular cartilage, but none has been effective in generating functional and long-lasting tissue [ 1 , 14 ]. Therefore, due to the high prevalence of OA and the urgent need for an effective treatment, the search for therapeutic alternatives, such as phytochemicals from plants and natural extracts, that can minimize side effects and be adapted to the progressive and multimodal character of OA has increased [ 1 , 15 ]. In fact, several natural compounds have shown anti-inflammatory potential, creating favorable conditions for the treatment development [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%